2019
DOI: 10.21608/zumj.2019.13392.1241
|View full text |Cite
|
Sign up to set email alerts
|

Letrozole versus Clomiphene Citrate with metformin for Induction of Ovulation in Obese patients with Polycystic Ovarian Disease

Abstract: Background: the polycystic ovary syndrome (PCOS) is important cause of an ovulatory infertility and a notable proportion of women of reproductive age are affected. Different factors could result in different manifestations and many of these are related to predispositions. Objectives: The study was carried out to study the improvement of ovulation induction in obese patients with Polycyctic ovarian syndrome (PCOS). Subjects and methods: This is prospective clinical trial that was conducted in the infertility un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Comparable results were detected in an Egyptian study that reported no significant difference between LE responders and non-responders regarding age, period of infertility, or BMI [ 46 ]. Another Egyptian study from 2019 found no significant association between the occurrence of pregnancy with either medication and the participants’ ages or BMIs [ 47 ]. A retrospective study conducted in Oman investigated the effect of LE combined with FSH on obese and non-obese women in achieving pregnancy and did not find a significant comparison [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Comparable results were detected in an Egyptian study that reported no significant difference between LE responders and non-responders regarding age, period of infertility, or BMI [ 46 ]. Another Egyptian study from 2019 found no significant association between the occurrence of pregnancy with either medication and the participants’ ages or BMIs [ 47 ]. A retrospective study conducted in Oman investigated the effect of LE combined with FSH on obese and non-obese women in achieving pregnancy and did not find a significant comparison [ 48 ].…”
Section: Discussionmentioning
confidence: 99%